Respuesta:
p() = 4
q(-2/3) = \frac{-65}{27}[/tex]
Explicación paso a paso:
p(x) =
p() =
4
Q(x) = - + 5x + 1
Q(-2/3) =
-(-8/27) - 10/3 + 1
8/27 - 10/3 + 1
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2024 KUDO.TIPS - All rights reserved.
Respuesta:
p(
) = 4![\sqrt{2}-13 \sqrt{2}-13](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D-13)
q(-2/3) = \frac{-65}{27}[/tex]
Explicación paso a paso:
p(x) =![x^{3}-5x^{2}+2x-3 x^{3}-5x^{2}+2x-3](https://tex.z-dn.net/?f=x%5E%7B3%7D-5x%5E%7B2%7D%2B2x-3)
p(
) = ![(\sqrt{2})^{3}-5(\sqrt{2}) ^{2}+2\sqrt{2}-3 (\sqrt{2})^{3}-5(\sqrt{2}) ^{2}+2\sqrt{2}-3](https://tex.z-dn.net/?f=%28%5Csqrt%7B2%7D%29%5E%7B3%7D-5%28%5Csqrt%7B2%7D%29+%5E%7B2%7D%2B2%5Csqrt%7B2%7D-3)
4![\sqrt{2}-13 \sqrt{2}-13](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D-13)
Q(x) = -
+ 5x + 1
Q(-2/3) =![-(-2/3)^{3}+5(-2/3)+1 -(-2/3)^{3}+5(-2/3)+1](https://tex.z-dn.net/?f=-%28-2%2F3%29%5E%7B3%7D%2B5%28-2%2F3%29%2B1)
-(-8/27) - 10/3 + 1
8/27 - 10/3 + 1